Word-Formation Patterns of Ancient Armenian Names of Ritual Objects - Karapetyan, Sirarpi (Bulletin of Yerevan University B: Philology, 2024)
Armenian ecclesiastical culture significantly influences various aspects of Armenian spiritual life, touching upon ethical, philosophical, literary, and historiographical domains. The translations of the Old and New Testaments, which provided the Armenian language with terms and flexible Armenian expressions of those various fields, in turn, contributed to the further development of independent and translated literature. The present article explores Ancient Armenian names of ritual objects and the development of their word-formation patterns in Armenian. The examination of words expressing ritual meaning is interesting not only from the linguistic point of view but also from historical, ethnographic, and cultural points of view. The ritual terms we have examined are compound and derivative. Armenian, known for its lexical versatility and expansive semantic range, demonstrates remarkable productivity in ritual terminology, showcasing substantial interconnectedness within its lexical framework. Ritual objects have long been integral to human cultural and spiritual practices, serving not only as implements for ceremonial rituals but also as potent symbols imbued with profound significance. For many individuals, these artifacts symbolize personal connections to faith and cultural identity, serving as tangible expressions of one’s heritage and values. Passed down through generations, they play a pivotal role in preserving and reinforcing familial traditions and religious beliefs.